2016
DOI: 10.1007/s10577-016-9521-0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific genome instability in synthetic interspecific hybrids of Pennisetum purpureum (Napier grass) and Pennisetum glaucum (pearl millet) is caused by micronucleation

Abstract: Genome instability is observed in several species hybrids. We studied the mechanisms underlying the genome instability in hexaploid hybrids of Napier grass (Pennisetum purpureum R.) and pearl millet (Pennisetum glaucum L.) using a combination of different methods. Chromosomes of both parental genomes are lost by micronucleation. Our analysis suggests that genome instability occurs preferentially in meristematic root tissue of hexaploid hybrids, and chromosome elimination is not only caused by centromere inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…capillaris [3]. In addition to mutagenesis, this strategy has been also applied by dos Reis et al in their study of tissue-specific instability in synthetic interspecific Pennisetum hybrids [48]. In the case of Brachypodium, 7% of the micronuclei with one telomeric and one centromeric signal were observed.…”
Section: Resultsmentioning
confidence: 99%
“…capillaris [3]. In addition to mutagenesis, this strategy has been also applied by dos Reis et al in their study of tissue-specific instability in synthetic interspecific Pennisetum hybrids [48]. In the case of Brachypodium, 7% of the micronuclei with one telomeric and one centromeric signal were observed.…”
Section: Resultsmentioning
confidence: 99%
“…), failures in spindle fibers formation and absence of metaphase plate were noted in the induced polyploids, as well as micro nuclei were observed in subsequent generation showing abnormalities in meiotic divisions [72]. Homoploid Pennisetum purpureum (L.) Brown × Pennisetum glaucum (L.) Brown showed alteration in karyotypes, as chromosomal rearrangement and loss of DNA sequences, thus evidencing that interspecific hybrids showing intergenomic conflicts could lose genomic DNA [73], including genes and DNA sequences of the centromere and telomere. Contrary to these findings, induced polysomic tetraploids of Italian or annual ryegrass (Festuca perennis Lam.…”
Section: Stability Of Induced Polyploidymentioning
confidence: 96%
“…However, the gene balance hypothesis raised by Birchler et al (31,32) indicates that genes on chromosomal segments can show dosage, compensation or inverse dosage effects, which obscured the general expectation of dosage effect. Moreover, it is important to note that aneuploidy contributes to phenotypic variations and the rapid morphological divergence of plants in the progeny population derived from new polyploidization (33). Studies have suggested that aneuploidy has a significant impact on phenotypic variability, including sterility (34), flowering time (35), and disease resistance (36), by introducing alterations in gene expression via gene dosage effects/compensation and by break-associated position effects (28).…”
Section: Introductionmentioning
confidence: 99%